Fabrication and evaluation of ribavirin-loaded electrospun nanofibers as an antimicrobial wound dressing - Khulud A. Alsulami; Abrar A. Bakr; Abdullah A. Alshehri; Alhassan H. Aodah; Fahad A. Almughem; Ali A. Alamer; Lujain A. Alharbi; Deema S. Alsuwayeh; Abdulrahman A. Halwani; Abdullah A. Alamoudi; Haya A. Alfassam; Essam A. Tawfik (Elsevier, 2024)
Background: Skin is regarded as an essential first line of defense against harmful pathogens and it hosts an ecosystem of microorganisms that create a widely diverse skin microbiome. In chronic wounds, alterations in the host-microbe interactions occur forming polymicrobial biofilms that hinder the process of wound healing. Ribavirin, an antiviral drug, possesses antimicrobial activity, especially against Pseudomonas aeruginosa and Candida albicans, which are known as the main opportunistic pathogens in chronic wounds. Rationale: In this study, electrospun nanofiber systems loaded with ribavirin were developed as a potential wound dressing for topical application in chronic wounds. Ribavirin was chosen in this study owing to the emerging cases of antimicrobial (antibiotics and antifungal) resistance and the low attempts to discover new antimicrobial agents, which encouraged the repurposing use of current medication as an alternative solution in case of resistance to the available agents. Additionally, the unique mechanism of action of ribavirin, i.e., perturbing the bacterial virulence system without killing or stopping their growth and rendering the pathogens disarmed, might be a promising choice to prevent drug resistance. Cyclodextrin (CD) was utilized to formulate ribavirin as an electrospun nanofibers delivery system to enhance the absorption and accelerate the release of ribavirin for topical use. Results: The results demonstrated a successful ribavirin nanofibers fabrication that lacked beads and pores on the nanofibrous surfaces. Ribavirin underwent a physical transformation from crystalline to amorphous form, as confirmed by X-ray diffraction analysis. This change occurred due to the molecular dispersion after the electrospinning process. Additionally, the CD enhanced the encapsulation efficiency of ribavirin in the nanofibers as observed from the drug-loading results. Polyvinylpyrrolidone (PVP) and CD increased ribavirin released into the solution and the disintegration of fibrous mats which shrank and eventually dissolved into a gel-like substance as the ribavirin-loaded fibers began to break down from their border toward the midpoint. Cytotoxicity of ribavirin and CD was evaluated against human dermal fibroblasts (HFF-1) and the results showed a relatively safe profile of ribavirin upon 24-hour cell exposure, while CD was safe within 24- and 48-hour. Conclusion: This study provides valuable insights into the potential application of our nanofibrous system for treating chronic wounds; however, further antimicrobial and in-vivo studies are required to confirm its safety and effectiveness.